Neutron and X-ray scattering studies of honeycomb iridates - Choi, S (2014)
This thesis presents neutron and x-ray scattering measurements on quasi-two-dimensional honeycomb antiferromagnets A2IrO3 (A=Na, Li) and the solid-solution intermediate material (Na1-xLix)2IrO3. The aim is to study the magnetic order and excitations of 5d Ir4+ ions in a honeycomb lattice, where unusual magnetic properties have been theoretically predicted to be stabilised by the combinations of strong spin-orbit coupling and honeycomb lattice geometry with 90 degree Ir-O-Ir bonding. By using an optimised setup to minimise the strong neutron absorption by Ir nuclei, inelastic neutron scattering measurements on powder sample of Na2IrO3 observed dispersive excitations below 5meV with a dispersion that can be accounted for by including substantial further-neighbor exchanges that stabilize zigzag magnetic order. The onset of long-range magnetic order was confirmed by the observation of oscillations in zero-field muon-spin rotation experiments. Higher-resolution inelastic neutron data found features consistent with a spin gap of 1.8meV and the data was parameterised by including Ising-type exchange anisotropy. Combining single-crystal diffraction and density functional calculations, a revised crystal structure model with significant departures from the ideal 90 degree Ir-O-Ir bonds required for dominant Kitaev exchange was proposed. Various "idealised'' crystal structures were constructed to emphasize the departures between the actual structure and structures with cubic IrO6 octahedra. The magnetic excitations from the isostructural Li2IrO3 revealed strongly dispersive magnetic excitations, qualitatively different from Na2IrO3. Elastic neutron diffraction detected a magnetic Bragg peak with a wavevector consistent with spiral orders. To explain the observed neutron data, the spiral H2 phase in the Heisenberg J1-J2-J3 model was proposed, and a full calculation was performed with strong in-plane anisotropic interaction. A further measurement for improving the lower-energy excitation found no clear evidence for a spin gap down to E=0.7meV. Lastly, the crystal structure of (Na1-xLix)2IrO3 was investigated with single-crystal x-ray diffraction, revealing a site-mixing of Ir and Na ions in the honeycomb lattice and insensitivity of the refinement to the Li positions. Ab initio calculations suggested that up to x=0.25 Li ions replaced Na in the honeycomb centre and phase separation occurred beyond that, which is consistent with the evolution of observed lattice parameters.